A Rare Case of Granulicatella adiacens Vertebral Osteomyelitis - E. van der Palen; C. L. M. de Roij van Zuijdewijn; D. A. R. Castelijn; G. H. Wattel-Louis; J. Kalpoe (Case Reports in Infectious Diseases)
Vertebral osteomyelitis caused by Granulicatella adiacens is rarely described. We report a 45-year-old immunocompetent male with back pain caused by G. adiacens osteomyelitis. This case is remarkable due to the absence of endocarditis. A clinician should therefore consider G. adiacens osteomyelitis even in the absence of concurrent hematogenous spread.